2015 10th International Conference for Internet Technology and Secured Transactions (ICITST) 2015
DOI: 10.1109/icitst.2015.7412113
|View full text |Cite
|
Sign up to set email alerts
|

RAT-based malicious activities detection on enterprise internal networks

Abstract: The detection of APT has recently become an urgent problem needing to be resolved. Attackers use Remote Access Trojan/Remote Administration Tools (RATs), which often bypass general security measures, and the traditional detection techniques don't consider reconnaissance activities after RAT infections. We analyzed the behavior of the reconnaissance for this paper so that RAT-based malicious activities on internal networks can be divided from the operations of normal users. Based on the features of their behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…In contrast with conventional Trojans, RATs have the capability to provide unauthorized access and control over a system through remote connections, without the host's knowledge (Yamada et al, 2015). This article will focus on the complexity of RATs aiming to identify files infected with them by relying on the texture derived from the transformation of executables into images.…”
Section: Theoretical Notions About Remote Access Trojans (Rats)mentioning
confidence: 99%
“…In contrast with conventional Trojans, RATs have the capability to provide unauthorized access and control over a system through remote connections, without the host's knowledge (Yamada et al, 2015). This article will focus on the complexity of RATs aiming to identify files infected with them by relying on the texture derived from the transformation of executables into images.…”
Section: Theoretical Notions About Remote Access Trojans (Rats)mentioning
confidence: 99%
“…To detect RAT with high accuracy, it is necessary to study and analyze every behaviour of the RAT. As mentioned in [35], most existing RATs have the functions of the killing process, editing registry, searching file, executing program, uploading files, sustaining connection and so on. By analyzing these functions from the perspective of detection, it can be found that the behaviours of killing process, editing registry and searching file can be detected by using appropriate host-side features because the execution of these functions left more traces on the host than on the network.…”
Section: Host-side and Network-side Detectionsmentioning
confidence: 99%
“…Yamada et al [15] presented an approach for raising alarms for hosts with reconnaissance in their network pattern activities, which compromise other hosts using administrative network protocols. Wu et al [16] introduced a framework for detecting RAT bots at the network gateway.…”
Section: Related Workmentioning
confidence: 99%
“…On the other hand, successful detection of infection resulted from the botminer framework [14] needs a large number of infected machines in the same network while the proposed collaborative framework gets over this requirement by using heuristic and machine learning techniques to detect even one infected machine in the monitored network. For the competitive framework in [15], a RAT botnet is detected by analyzing the network traffic to get specific management protocol commands for botnet detection. This could limit the detection capabilities specifically for RAT bots that do not use such types of commands.…”
Section: A Comparison With Competitive Adversarial Frameworkmentioning
confidence: 99%